The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jacc.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Control of Heart Rate and QT Interval Variability Influences Arrhythmic Risk in Long QT Syndrome Type 1

Abstract: BACKGROUND A puzzling feature of the long QT syndrome (LQTS) is that family members carrying the same mutation often have divergent symptoms and clinical outcomes. OBJECTIVES We tested the hypothesis that vagal and sympathetic control, as assessed from spectral analysis of spontaneous beat-to-beat variability of RR and QT intervals from standard 24-hour electrocardiogram Holter recordings, can modulate the severity of LQTS type 1 (LQT1) in 46 members of a South-African LQT1 founder population carrying the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 33 publications
4
62
0
Order By: Relevance
“…This finding suggests that AMCs are also different from NMCs, thus allowing us to hypothesize that AMCs have a peculiar genetic make-up playing a significant role in limiting the severity of their disease and providing them a key advantage for survival with respect to SMCs. This conclusion supports previous observations about the differences of the sympathetic modulation among NMCs, AMCs and SMCs [45], reporting that the sympathetic control is higher in AMCs, while those of NMCs and SMCs are similar. It is noteworthy that traditional time domain indexes utilized in clinics [18,19,46] cannot distinguish AMCs from SMCs (Table 1).…”
Section: Rmsce and Rmsse Distinguish Lqt1 Individuals With Different supporting
confidence: 92%
See 2 more Smart Citations
“…This finding suggests that AMCs are also different from NMCs, thus allowing us to hypothesize that AMCs have a peculiar genetic make-up playing a significant role in limiting the severity of their disease and providing them a key advantage for survival with respect to SMCs. This conclusion supports previous observations about the differences of the sympathetic modulation among NMCs, AMCs and SMCs [45], reporting that the sympathetic control is higher in AMCs, while those of NMCs and SMCs are similar. It is noteworthy that traditional time domain indexes utilized in clinics [18,19,46] cannot distinguish AMCs from SMCs (Table 1).…”
Section: Rmsce and Rmsse Distinguish Lqt1 Individuals With Different supporting
confidence: 92%
“…This finding suggested that having a reduced complexity of the cardiac control both at the level of sinus node and ventricles during DAY (i.e., when the arrhythmic risk is greatest in LQT1) is a protective factor [13]. Since AMCs are characterized by a more reactive sympathetic control [45] and a less reactive vagal regulation [45][46][47], this reduced complexity of the sympathetic control might be the result of the synchronization of neural inputs operating at slightly different temporal scales performed by the higher sympathetic driver [43,48]. However, this study added a new, relevant, piece of information.…”
Section: Rmsce and Rmsse Distinguish Lqt1 Individuals With Different mentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches to assess repolarization variability use parametric modeling [42], [75], [76]. While in [76] Porta et al investigate variability of the RT interval, in [42] Almeida et al explore QTV, and in [75] the variability from the R peak to the T wave end (RTe) is considered. The use of RT instead of QT avoids the need to determine the end of the T wave, which is usually considered to be problematic.…”
Section: ) Qt Adaptation To Hr Changesmentioning
confidence: 99%
“…The association between increased repolarization variability and risk for VT/VF was also shown in [80] for post-MI patients with severe left ventricular (LV) dysfunction. In [75] an index quantifying autonomic control of HR and RTe was shown to separate symptomatic LQTS carriers from asymptomatic ones and controls.…”
Section: ) Qt Adaptation To Hr Changesmentioning
confidence: 99%